Identifikasi Kandungan Unsur pada Pasir Kuarsa Menggunakan Metode X-Ray Flourescence di Kecamatan Samadua, Aceh Selatan : Identification of Elemental Contents in Quartz Sand Using the X-Ray Flourescence Method in Samadua District, South Aceh - Bakruddin, Bakruddin; Rachmatillah, Faukas; Amri, Asbahrul; Jalil, Zulkarnain (Jurnal Jejaring Matematika dan Sains, 2020)
Quartz sand is a non-metallic natural resource that can be used to develop various kinds of human needs, however, it is necessary to know in advance the amount and elements contained therein. This research will conduct a study related to the amount of element concentration in quartz sand in Samadua District, South Aceh Regency. The research method used in this research is the X-Ray Fluorescence technique. The results showed that the elements found in the quartz sand samples were Si, K, Ca, Ti, V, Cr, Mn, Fe, Cu, Sr, Ba, and Eu. From these results, there are three elements that have the highest concentration, namely the element Si as much as 62%, Ca as much as 15.7%, and element K as much as 13.7%.